PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS XI IPA 2 DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIF LEARNING TIPE JIGSAW - Rahman, Sitti Aliyah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This research is classroom action research with exposure of the functionality of the descriptive of the quality is categimized in the form of cumulative frequency data, the subjects of the study are students of class XI IPA 2 MAN Suli distrie Luwu school year 2016/2017, data collection with observation and test techniques. The results of this study indicate that learning bu using Cooperative Learning type Jigsaw method can improve student achievement in Mathematics class XI IPA 2 MAN Suli Luwu Regency school year 2016/2017.In connection with this, the researcher suggested that the teacherof class XI IPA 2 MAN Suli, Luwu Regency, can apply learning using the Cooperative LearningÂ  type Jigsaw method in presenting learning materials in order to optimize the ability of studets to solve Math problem questions.Â Keywords: Mathematic Learning Result, Model Cooperative Learning Type Jigsaw.Â